Light of the jedi ebook - Soule, Charles (Star Wars: The High Republic Novels., 2021)
#1 NEW YORK TIMES BESTSELLER • Long before the First Order, before the Empire, before even The Phantom Menace  . . . Jedi lit the way for the galaxy in The High Republic It is a golden age. Intrepid hyperspace scouts expand the reach of the Republic to the furthest stars, worlds flourish under the benevolent leadership of the Senate, and peace reigns, enforced by the wisdom and strength of the renowned order of Force users known as the Jedi. With the Jedi at the height of their power, the free citizens of the galaxy are confident in their ability to weather any storm But the even brightest light can cast a shadow, and some storms defy any preparation. When a shocking catastrophe in hyperspace tears a ship to pieces, the flurry of shrapnel emerging from the disaster threatens an entire system. No sooner does the call for help go out than the Jedi race to the scene. The scope of the emergence, however, is enough to push even Jedi to their limit. As the sky breaks open and destruction rains down upon the peaceful alliance they helped to build, the Jedi must trust in the Force to see them through a day in which a single mistake could cost billions of lives. Even as the Jedi battle valiantly against calamity, something truly deadly grows beyond the boundary of the Republic. The hyperspace disaster is far more sinister than the Jedi could ever suspect. A threat hides in the darkness, far from the light of the age, and harbors a secret that could strike fear into even a Jedi’s heart.